Implications of physical fitness level on sport injury - Mauro Tanaka Riyis , Juliana Piazza Fermi; Luís Felipe Milano Teixeira; Vladimir Juliano de Godoi; Luiz Carlos de Barros Ramalho; Élio Fernandes Más; Marcelo Conte; Sérgio Paulo de Tarso Domingues; Juliana Piazza Fermi (Universidade Federal de Santa Catarina, 2005)
The aim of this cross-sectional study was to verify associations between the physical fitness level and Sports Injuries (SI). One hundred-sixty-two athletes who played in the official teams of Sorocaba City, state of São Paulo, were investigated. Physical fitness and SI was configured as an independent and dependent variables, respectively. Contingency analyses were performed, using SI as an effect and either percent of body fat, muscular endurance (upper limb and abdominal), flexibility and sports modality characteristic (individual or team) as the exposure. The Odds Ratio (OR) and their respective Confidence Intervals (IC) were calculated. The results revealed lack of association between SI and sex. The following OR values for SI were observed in athletes who showed percent of body fat above the mean (2.24); low flexibility (2.36); reduced upper limb muscular endurance (2.35) and played team modalities (4.23). It can be concluded that, regardless of sex, athletes were at a higher risk for SI if they had higher body fat, less flexibility, lower upper limb muscular endurance and participated team sports. Therefore, it is suggested that physical fitness must be considered as a strategy for SI prevention. RESUMO O objetivo deste estudo foi verificar a associação entre o nível de aptidão física e lesões desportivas (LD). Foram investigados 162 atletas, integrantes das equipes de representação da cidade de Sorocaba/SP. Tratou-se de estudo transversal, configurando-se como variável independente a aptidão física e como dependente as LD procedeu-se à análise de contingência, considerando LD como efeito e percentual de gordura corporal, resistência muscular abdominal e de membros superiores (MMSS), flexibilidade e característica da modalidade (individual ou coletiva) como exposição, de sorte que Odds Ratio (OR) e respectivos Intervalos de Confiança (IC) foram calculados por relação de distribuição diferencial. Os principais resultados revelaram ausência de associação entre LD e sexo, neste sentido: i) atletas com percentual de gordura acima da média referencial, apresentaram OR = 2,24 de LD; ii) atletas com baixa flexibilidade apresentaram OR = 2,36 de LD; iii) atletas com resistência muscular de MMSS reduzida revelaram OR = 2,35 de LD e iv) praticantes de modalidades coletivas mostraram risco 4,23 maior de LD do que os atletas de modalidades individuais. A partir destes resultados pode-se concluir que, independentemente do sexo, os atletas com gordura corporal elevada, baixa flexibilidade, resistência muscular de MMSS reduzida e que praticam modalidades coletivas, apresentaram risco aumentado de se lesionarem.